Towards standardisation of no fault found taxonomy - Khan, Samir; Phillips, Paul; Hockley, Chris; Jennions, Ian K. (Cranfield University, 2012)
There is a phenomenon which exists in complex engineered systems, most notably those which are electrical or electronic which is the inability to diagnose faults reported during operation. This includes difficulties in detecting the same reported symptoms with standard testing, the inability to correctly localise the suspected fault and the failure to diagnose the problem which has resulted in maintenance work. However an inconsistent terminology is used in connection with this phenomenon within both scientific communities and industry. It has become evident that ambiguity, misuse and misunderstanding have directly compounded the issue. The purpose of this paper is to work towards standardisation of the taxonomy surrounding the phenomena popularly termed No Fault Found, Retest Okay, Cannot Duplicate or Fault Not Found amongst many others. This includes discussion on how consistent terminology is essential to the experts within organisation committees and, to the larger group of users, who do not have specialised knowledge of the field.